Privacy and Social Media: Defining Privacy in the Usage of Path - Fandia Purwaningtyas, Mashita Phitaloka (KnE Social Sciences, 2019)
The existence of social media has changed the landscape of human’s relationship. Through social media, people are able to present many versions of themselves in many platforms. In this era of polymediation of the self, the discussion regarding to privacy becomes arguable, moreover, with the presence of Path; a social media platform which presents itself as a private social media. Hence, in the sociocultural context of Indonesian society, it is important to see how the definition of privacy is constructed by the existence of Path. Therefore, this research is conducted in order to analyze and explore how privacy is perceived by the social media users nowadays, particularly the users of Path, and why they perceive it in that certain way. This research is conducted with ethnography as the main method and virtual ethnography as the supporting method. From the research, it is found that users’ way of defining privacy is embodied in two levels: online self-presentation and personal space construction. In the first level, the stages of privacy offered by Path have created the fragmented-self among users. This fragmentation has resulted in “the ambivalent self”, “self that desires recognition”, and “self that searches for freedom”. In the second level, the mediality of Path has served the users of the ability to construct their own personal space in social media space. This construction of the personal space has resulted in “space of comfort in similarity”, “space of pseudo-liberation”, and “space that demolishes the panoptic”. Henceforth, these findings lead to a conclusion that usage practices of social media has killed the authentic self and created a personal space that gives the sense of the absence of control, hierarchy, and social surveillance. Eventually, privacy for Path is defined by the process of exchange of “the self and personal information” with “social recognition, sense of equality, and reciprocal relationship”. Keywords: privacy, social media, ethnography, Path